The blue bowl - Leung, Flo (Owlkids Books, 2024)
"A young boy and his family discover a way to merge their Chinese and North American backgrounds by combining traditional foods from both cultures. Max loves his family's Cantonese meals, like steamed rice and gai lan greens with oyster sauce, homemade dumplings, and scallion bread. But sometimes he can't help thinking about French fries, tacos, and ice cream with rainbow sprinkles. For his birthday dinner, Max is really hoping for spaghetti and meatballs, but instead he and his family are headed to Maa Maa and Ye Ye's house for a celebration dinner - and Max is pretty sure that spaghetti won't be served in the familiar blue bowls that came all the way from Hong Kong with his grandparents. But Max is delighted to discover that his understanding family has discovered a way to bring two cultures together with delicious dishes that are a combination of all the foods he loves. This story shows the experience of a child living in between two cultures and how confusing that can sometimes be. It's based on Flo's own experiences growing up, longing to belong/be organically part of the North American culture, but also feeling a strong sense of home and family when immersed in her Chinese culture. She feels that the result for many second-generation Chinese Canadians/Americans is the creation of a third culture that intertwines and connects the various influences of both. Flo has chosen the iconic "exquisite blue bowl" (that she says would be familiar to many Chinese-American families) and the food that goes inside that bowl to set the stage for this duality in the story. Max is trying to come to terms with where he fits in these two cultures, and by the end the story, with the help of his family, he discovers that he has the freedom to create his own experiences, and the results are unique, interesting, and evolving - just like Max himself."--